Yahoo Answers: Answers and Comments for Solve x2 + 7x + 6 = 0 for x? [Mathematics]
Copyright © Yahoo! Inc. All rights reserved.
https://answers.yahoo.com/question/index?qid=20061229190237AA1IAgj
From shawntaelsey123
enUS
Fri, 29 Dec 2006 19:02:37 +0000
3
Yahoo Answers: Answers and Comments for Solve x2 + 7x + 6 = 0 for x? [Mathematics]
292
38
https://answers.yahoo.com/question/index?qid=20061229190237AA1IAgj
https://s.yimg.com/zz/combo?images/emaillogous.png

From stewartlucas467: x^2 + 7x + 6 = 0
(x + 1)(x + 6) = 0
(x + 1) ...
https://answers.yahoo.com/question/index?qid=20061229190237AA1IAgj
https://answers.yahoo.com/question/index?qid=20061229190237AA1IAgj
Sat, 30 Dec 2006 03:26:29 +0000
x^2 + 7x + 6 = 0
(x + 1)(x + 6) = 0
(x + 1) = 0 or (x + 6) = 0
x = 1 x = 6

From yupchagee: x^2 + 7x + 6 = 0
(x+6)(x+1)=0
x+6=0
x=6
x...
https://answers.yahoo.com/question/index?qid=20061229190237AA1IAgj
https://answers.yahoo.com/question/index?qid=20061229190237AA1IAgj
Sat, 30 Dec 2006 03:19:07 +0000
x^2 + 7x + 6 = 0
(x+6)(x+1)=0
x+6=0
x=6
x+1=0
x=1
x=6, 1

From modulo_function: I presume that you mean x^2 for the first term...
https://answers.yahoo.com/question/index?qid=20061229190237AA1IAgj
https://answers.yahoo.com/question/index?qid=20061229190237AA1IAgj
Sat, 30 Dec 2006 03:08:42 +0000
I presume that you mean x^2 for the first term.
It's a 2nd order polynomial and so has two solutions, not necessarily different.
I'd advise factoring rather than resorting to the lazy person's quadratic formula.
So, can you think of two numbers whose:
product is 6
and
sum is 7
?
(I'll wait.....)
So, those two numbers, r1 and r2, are the roots or solutions of the equation:
x^2+7x+6 = 0
(xr1)*(xr2) = 0
Ta da....

From JAC: this is factorable..
(x+1)(x+6)=0
and usin...
https://answers.yahoo.com/question/index?qid=20061229190237AA1IAgj
https://answers.yahoo.com/question/index?qid=20061229190237AA1IAgj
Sat, 30 Dec 2006 03:06:37 +0000
this is factorable..
(x+1)(x+6)=0
and using the zero product rule, which says, A*B=0 if A=0 or B=0..
upon setting x+1 =0
and x+6=0
we get x=1
and x= 6

From Anonymous: You need to factor the problem:
(x+6)(x+1)=0
...
https://answers.yahoo.com/question/index?qid=20061229190237AA1IAgj
https://answers.yahoo.com/question/index?qid=20061229190237AA1IAgj
Sat, 30 Dec 2006 04:18:05 +0000
You need to factor the problem:
(x+6)(x+1)=0
x=6 or 1